PERSEPSI HOSPITALITY INDUSTRI TERHADAP KOMPETENSI MAHASISWA MAGANG DALAM PELAKSANAAN PRAKTEK INDUSTRI: PERSEPSI HOSPITALITY INDUSTRI TERHADAP KOMPETENSI MAHASISWA MAGANG DALAM PELAKSANAAN PRAKTEK INDUSTRI - Eka Rachmawati (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2025)
The purpose of this study was to determine the competencies required in thehospitality industry. The sample consisted of 10 hotels, 5 in Greater Jakarta and5 in Yogyakarta Special Region, and 6 restaurants, 3 in Greater Jakarta and 3in Yogyakarta Special Region, which served as industrial internship locations.Data collection took place from September to November 2024. The instrumentused was a questionnaire created with Google Forms, which was validated usingan r-value of 0.620 and a variable reliability test of 0.754. The data analysistechnique used was quantitative descriptive analysis. Criteria were determinedbased on the Assessment Reference Standard (PAP). The results showed that thehotel and restaurant industry's perception of the competencies required byinternship students was: good communication skills (average 85), teamworkskills (average 87), adaptability (average 82), customer service skills (average88), and multitasking skills (average 87). All competency indicators were in thehigh category, with averages above 80.